Rekontekstualisasi Filsafat Islam dalam Kurikulum Madrasah untuk Penguatan Nalar Kritis dan Pembentukan Insan Kamil - Lesmana, Surya (Yayasan Albahriah Jamiah Indonesia, 2025)
The madrasah curriculum in contemporary Islamic education faces the challenge of balancing the normative-religious dimension with the need to strengthen students’ critical reasoning skills. Islamic philosophy, as an intellectual tradition characterized by essential, integrative, and rational reflection, is often marginalized in formal education due to ideological resistance, limited teaching staff, and a lack of understanding of its importance in shaping a complete human being. This study aims to re-examine the importance of recontextualizing Islamic philosophy in the madrasah curriculum as a means of strengthening critical thinking skills while shaping a holistic personality. Using qualitative methods based on literature studies and descriptive-analytical analysis, this study compiles relevant primary and secondary sources on the discourse of Islamic philosophy and madrasah curriculum development. The results of the study indicate that Islamic philosophy has significant potential to integrate cognitive, affective, and spiritual aspects into the learning process. This integration has been proven to encourage students to develop analytical, reflective, and solution-oriented thinking skills in facing contemporary issues from a comprehensive Islamic perspective. Furthermore, teachers equipped with philosophy training can develop dialogue-based learning, open up intellectual discourse, and connect religious texts with real-life contexts. This study concludes that Islamic philosophy plays a strategic role in transforming the madrasah curriculum, as it can foster an educational model based on wisdom, spirituality, and rationality, ultimately supporting the formation of a perfect human being, the ideal goal of Islamic education.